Fatigue life assessment for a welded detail: advantages of a local energetic approach and experimental validation (Fracture and Structural Integrity, 2018)
In modern civil buildings, as well as in mechanical and naval constructions, welding is a widely diffused technological process. The fatigue assessment, as design or verification procedure, of a welded joint to evaluate his endurance with respect to a load spectrum is a challenging but of paramount importance procedure. Several techniques have been proposed in the literature, constantly researching efficient, cost effective and reliable methods to predict the behavior of a complex welded structures. Some of them are part of norms and standards which any design engineer must respect. The aim of the present work is to compare the results provided by some of the principal fatigue life assessment procedures for welded joints, focusing the attention on the stress intensity factor evaluation by the use of numerical methods. Finally the proposed numerical method has been experimentally validated.
Keywords: Welding; Fatigue; Strain energy density; Crack initiation; Structural steel; Finite Element Analysis